Shock to Initiation Characters of Heated Explosives with Different Confinement. Issue 2 (18th December 2015) - Wang, Chen; Chen, Lang; Wu, Jun‐Ying; Liu, Qun; Hu, Xiao‐Mian
Abstract: Heated explosives might undergo thermal expansion and/or phase transition, which affects their shock sensitivity. Therefore, investigating the effect of temperature on the shock initiation properties of explosives would provide valuable safety guidelines for their transportation and handling. In this study, an experimental detonation device that achieved homogeneous heating of the explosive test sample while avoiding unintended heat transfer to the donor was designed and constructed. The device allowed to perform flyer impact tests on PBXC10 at different temperatures and using different confinement conditions. The generated experimental pressure history curves were used to calculate the parameters of the I&G model and determine their relationships with the sample temperature. The fully parameterized I&G model enabled predicting the shock initiation properties of PBXC10 at temperatures where experimental data were unavailable. It was concluded that increased sample temperatures would lead to a shorter run distance to detonation, faster propagation of the detonation wave and enhanced shock sensitivity of the explosive. It was also demonstrated that unconfined PBXC10 exhibited significantly greater shock sensitivity compared to its partially and completely confined counterparts. Abstract :